Joseph Ratzinger's "Kierkegaardian option" in "Introduction to Christianity" - Dinan, Matthew D. ca. 20./21. Jh. (International journal of philosophy and theology, 2019)
Although scholars increasingly recognize the debts of twentieth-century Roman Catholic theologians to Søren Kierkegaard, no one has yet traced this influence to Joseph Ratzinger (Pope Emeritus Benedict XVI). As is frequently observed, Ratzinger's most famous book, Introduction to Christianity, opens with a meditation on a Kierkegaardian parable from Either/Or. We argue that Ratzinger's use of Kierkegaard extends well beyond this opening image, to some central moments in his articulation of the idea of God, Christology, and theological anthropology. Upon closer inspection, we argue, Ratzinger's use of these arguments is owing to the fact that his diagnosis of the ills of contemporary society and the orientation of contemporary Christian theology is the same as that of Kierkegaard, despite their seemingly different contexts. Identifying the Kierkegaardian influence on Introduction to Christianity helps draw our attention to the necessarily ‘introductory' character of Christianity, which otherwise risks being lost.